2021
DOI: 10.1002/col.22698
|View full text |Cite
|
Sign up to set email alerts
|

Preference for accent and background colors in interior architecture in terms of similarity/contrast of natural color system attributes

Abstract: Color combination criteria are said to entail an affective response in interior design. We investigated the color combination criteria that orient the preference of current observers, after Le Corbusier's 1931 Salubra keyboards. We explored the similarity/contrast in Natural Color System (NCS) hue, blackness, and chromaticness in 312 combinations with four colors, two backgrounds and two accent colors, coming from 43 individual colors, on the walls of a simulated interior of a bedroom from the Swiss Pavilion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the study made by Serra et al, 46 the color tone, color code and color percentages were analyzed according to the Natural Color System (NCS) related to the best color combination preferences and the results of the findings obtained provided new viewpoints. Also, in our study, just as in the study, 46 the colors, color codes and color percentages were analyzed in the context of what would be applied to the building façades. Whereas in another study, 47 it contributed to understanding how the colors were formed and contained discussions related to different color combinations, and formation of color pairs.…”
Section: Conclusion and Evaluationmentioning
confidence: 99%
“…In the study made by Serra et al, 46 the color tone, color code and color percentages were analyzed according to the Natural Color System (NCS) related to the best color combination preferences and the results of the findings obtained provided new viewpoints. Also, in our study, just as in the study, 46 the colors, color codes and color percentages were analyzed in the context of what would be applied to the building façades. Whereas in another study, 47 it contributed to understanding how the colors were formed and contained discussions related to different color combinations, and formation of color pairs.…”
Section: Conclusion and Evaluationmentioning
confidence: 99%
“…Fourthly, there is exploring the functionality of color as the reason for its use in architecture and urban studies, that is, studying how color affects the visual perception of an objectits geometry, size, visual weight and texture, and the composition of its volumes-and thus increasing the space efficiency (Serra et al 2012(Serra et al , 2021(Serra et al , 2022Braham 2002;Serra 2013). This includes research into the history of national color schemes in the urbanscape (Brino 2010;Arrarte-Grau and Ludmir 1987;Wigley 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Mahmood and Tayib (2021) found through questionnaires that using diverse wall colors, beautiful tiles, and durable wall coatings in interior design could improve the psychological comfort of the user. Serra et al (2021) found that the psychological satisfaction of people with the environment was significantly enhanced when the colors of walls and floors were lighter shades or similar chroma. However, no study has been found on the relationship between the aesthetic preference of tile design and neural responses.…”
Section: Introductionmentioning
confidence: 99%